RESILIENSI IBU DARI ANAK DENGAN DOWN SYNDROME YANG BERPRESTASI DALAM BIDANG OLAHRAGA - Allicia Allicia; Made Dharmawan Rama Adhyatma (Universitas Katolik Widya Mandala Surabaya, 2020)
Down Syndrome is a disorder caused by chromosome abnormalities that are associated with mental retardation, characteristic facial appearance, and poor muscle. The disorder makes a child diagnosed with this disorder has a typical characteristic such as lower intellectual capability, social capability, and healthiness than the other child with normal development. The presence of a child with Down Syndrome makes the majority of mothers experience deep sadness, stress, and depression. That's why the capability to respond and accept the presence of the child positively is needed. Resilience is an individual capability to face, deal, and respond to difficulties or challenges in life in a healthy and productive manner. This study using qualitative research method with phenomenological approach. Informant in this study were three mothers which having a child with Down Syndrome that is achieved in sport. The informant was chosen with a purposive sampling method. This study using an inductive thematic analysis data analysis technique. The results of this study indicate that mothers who have Down Syndrome child’s see her child’s is a gifts, have a sense of pride in the child’s achievements, social support from those around her makes her have an optimism to develop children’s potential, and an effort to develop children’s interests and talents.